Predictive value of circulating fibroblast growth factor-23 and Klotho on protein-energy wasting in patients undergoing hemodialysis - Zhou, Xiaoling; Luo, Yang; Guo, Yidan; Jia, Meng; Zhang, Chunxia; Shi, Zhihua; Du, Ye (Frontiers in Nutrition, 2025)
BackgroundAs a state of metabolic and nutritional derangements, protein-energy wasting (PEW) is highly prevalent and associated with increased morbidity and mortality in hemodialysis patients. Fibroblast growth factor-23 (FGF-23) and Klotho have been proven to contribute to chronic kidney disease-mineral and bone disorder (CKD-MBD) in patients undergoing hemodialysis. Previous evidence suggested that FGF-23 and Klotho may also contribute to the malnutritional status among these patients; however, the inter-relationship between the FGF-23–Klotho axis and PEW remains unclear. Therefore, we conducted this cross-sectional study to evaluate the association between plasma FGF-23 and Klotho levels and PEW in hemodialysis patients and to explore whether these markers could predict the presence of PEW.MethodsPlasma concentrations of FGF-23 and Klotho were measured, and their associations with PEW were assessed. PEW was evaluated based on body weight, muscle mass, biochemical data, and protein and energy intake, according to the 2008 criteria from the International Society of Renal Nutrition and Metabolism (ISRNM).ResultsIn this study, 147 hemodialysis patients (mean age 61.05 ± 13.32 years) were enrolled, of whom 66 (44.90%) had PEW. PEW was significant positively correlated with FGF-23 (r = 0.403, p < 0.001), age (r = 0.225, p = 0.006), C-reactive protein (r = 0.236, p = 0.004), intact parathyroid hormone (r = 0.237, p = 0.004), and single-pool Kt/V (r = 0.170, p = 0.040), while it was negatively correlated with Klotho (r = −0.361, p < 0.001), hemoglobin (r = −0.215, p = 0.009), and serum creatinine (r = −0.278, p = 0.001). Logistic regression analyses showed that plasma FGF-23 and Klotho were independently associated with PEW, even after adjusting for covariables. The area under the ROC curve (AUC) of FGF-23 and Klotho in predicting PEW was 0.734 and 0.710 (p < 0.001), respectively. When the combination of FGF-23 and Klotho was used to predict PEW, its sensitivity was 81.8%, specificity was 60.5%, and the AUC was 0.746.ConclusionPlasma levels of FGF-23 and Klotho are associated with PEW in hemodialysis patients. Higher plasma FGF-23 levels and lower Klotho levels may serve as valuable predictors of PEW in these patients.